Simulation géostatistique séquentielle gaussienne de la distribution des teneurs en P2O5 dans le gisement de phosphate de Kef Essennoun, Bassin de Djebel Onk - SADOUN ,Houria; Dassamiour, M(Encadreur) (Université Ferhat Abbas Sétif 1. institut d'architecture et sciences de la terre. département de géologie, 2017)
The Kef Essennoun phosphate deposit is part of the Djebel Onk basin. It is located northwest of Tebessa, near to Bir El Ater city. It is a monoclinic layer with an average thickness of 35 m and is dated of the upper Thanetian. The Gaussian equential simulation was used for mapping the spatial distribution of P2O5 contents in this deposit. The varyographic analysis showed a geometric anisotropy of the distribution of P2O5 contents. This is related to the deposition mode of these phosphates in the form of elongated strata. The obtained model showed the concentration of the highest contents in the main layer and which is clamped between the two top and bottom layers which have the lower contents. This model helps in the orientation of the exploitation and the calculation of the reserves.
یقع منجم فوسفات كاف السنون و الذي ھو جزء من حوض جبل العنق شما ل غرب ولایة تبسة ، بالقرب من بلدة ببرالعاتر. و ھو یظھر كطبقة أحادیة المیل ذات سمك متوسط یقدر ب 35 م و عمر جیولوجي ھو الطانیسیا العلوي.في المنجم. تظھر التحالیل 􀜲􀬶􀜱􀬹 استخدام النمدجة المتتالیة لجوس بھدف تحدید خریطة توزیع نسب ال و یرتبط ھذا بطریقة ترسب و توضع الفوسفات على شكل 􀜲􀬶􀜱􀬹 الفاریوغرافیة تباینا ھندسیا لتوزع نسبة ال طبقات مبسوطة. یبین النموذج الناتج أن التركیز النسبي الأكبر یتواجد في الطبقة الرئیسة التي تقع بین كل من الطبقة العلویة و القاعدیة اللتان تحتویان على تراكیز أقل. إن ھذا النموذج یساعد على توجیھ استغلال المنجم وحساب الاحتیاطات
Keywords: Gisement de Kef Essennoun; Phosphate; Simulation séquentielle gaussienne; Distribution des teneurs en P2O5.